Youth identity and identities: : Talking about hope amidst the collapse of hope - Palazzi von Büren Félix (Razón y fe, 2022)
This article offers an approach to the subject of youth identity. In the current historical conditions, and in the face of the possibility of a civilizational decline, it is necessary to forge an intergenerational dialogue. The collapse of hope in a postsecular world invites us to rethink this attitude among all and with all.